Indonesia, Tiongkok dan Komunisme, 1949-1965 - Utomo, Satriono Priyo (Indonesian Perspective, 2017)
During the leadership of President Sukarno, China had an important meaning not only for the people of Indonesia but also as a source of political concept from the perspective of Sukarno. In addition, China also had significance for the Indonesian Communist Party (PKI) as a meeting room prior to communist ideology. The paper employs literary study method and discusses about diplomatic relations between Indonesia and China during the Guidance Democracy ( 1949-1965). The relationship between two countries at that time exhibited closeness between Sukarno and Mao Tse Tung. The political dynamics at that time brought the spirit of the New Emerging Forces. Both leaders relied on mass mobilization politics in which Mao used the Chinese Communist Party while Sukarno used the PKI.Keywords: Indonesia, China, diplomacy, politics, ideology, communism